Keutamaan Belajar Dan Mengajar Perspektif Hadits Nabi Muhammad SAW - Aripuddin; Abbas Baco Miro; Rahmi Dewanti; Nurkhalishah (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This study aims to examine the virtues of learning and teaching from the perspective of the hadith of Prophet Muhammad SAW. Using a qualitative approach with a library research method, this study analyzes hadith collections, Islamic education books, and scholarly journal articles related to hadith tarbawi. The findings indicate that learning and teaching hold a noble status in Islam and are considered acts of worship. Seeking knowledge is an obligation for every Muslim, while teaching knowledge is regarded as a continuous charity (amal jariyah). The hadiths also emphasize the importance of ethics, sincere intention, and exemplary conduct in the educational process. This study concludes that the values of hadith tarbawi remain relevant as a foundation for Islamic education oriented toward moral and intellectual development.AbstrakPenelitian ini bertujuan mengkaji keutamaan belajar dan mengajar dalam perspektif hadits Nabi Muhammad SAW. Penelitian menggunakan pendekatan kualitatif dengan metode studi kepustakaan terhadap kitab hadits, buku pendidikan Islam, dan artikel jurnal terkait hadits tarbawi. Hasil penelitian menunjukkan bahwa belajar dan mengajar memiliki kedudukan mulia dalam Islam dan bernilai ibadah. Menuntut ilmu merupakan kewajiban setiap Muslim, sedangkan mengajar merupakan amal jariyah yang pahalanya terus mengalir. Hadits Nabi juga menekankan pentingnya etika, niat, dan keteladanan dalam proses pendidikan. Kajian ini menegaskan bahwa nilai-nilai hadits tarbawi relevan sebagai landasan pendidikan Islam yang berorientasi pada pembentukan akhlak dan keilmuan.